Effects of ultrasonic removal of fractured files from the middle third of root canals on dentinal cracks: a micro‐computed tomography study. (30th March 2018) - Fu, M.; Huang, X.; He, W.; Hou, B.
Abstract: Aim: To evaluate the frequency of dentinal microcracks after ultrasonic removal of fractured files from the middle third of root canals using micro‐computed tomography (micro‐CT). Methodology: Eighteen bilaterally matched pairs of human mandibular incisors extracted for periodontal reasons were included. The matched pairs of teeth were then divided into a control group and an experimental group, with one member of each pair assigned to each group. In the control group, the canals were instrumented using the ProTaper Next (PTN) system. In the experimental group, size 20 K‐files were fractured in the middle third of the root canals, followed by their ultrasonic removal. Subsequently, the canals were instrumented with the PTN system. All teeth were scanned using high‐resolution micro‐CT before (preoperative) and after (intraoperative) file removal and after (postoperative) root canal preparation. Pre‐, intra‐, and postoperative cross‐sectional images of the roots were screened to identify the presence of dentinal defects. Two experienced observers evaluated the images twice in a blinded manner. The incidence of dentinal microcracks was noted and statistically analysed using Fisher's exact and McNemar's tests ( P  =   0.05), with the root cross‐section and the tooth root as the units of analysis, respectively. Results: All fractured files in the experimental group were removed successfully. New microcracks were detected in 0.56% (93/16 472) cross‐sections (8/18 specimens) generated after file removal in the experimental group. These microcracks were detected 4–6 mm below the root canal orifice and exhibited a width and length of 12–36 μm and 48–72 μm, respectively. They did not disappear or propagate after canal preparation. No new dentinal microcracks were observed in the control group. There was a significant difference in the incidence of new microcracks between the two groups ( P  <   0.05). Conclusions: Ultrasonic removal of fractured files from root canals resulted in the formation of short microcracks in a small number of cross‐sections in approximately half the specimens. Further studies are necessary to determine the cause and consequences of this finding.